NFT Communities as Societies of Producers - Serada, Alesha (Routledge, 2024)
At least for a short period of time at the beginning of 2020s, non-fungible tokens (NFTs) achieved recognition as a potential tool for rebuilding creative economies. Blockchain evangelists saw them as the step upward from the so-called Web 2.0, the internet of user-generated content, to Web 3.0, a fully decentralized network where creators are in control of their output and benefit from it directly. In the wake of so-called Web 3.0, the focus has shifted even further, from consuming digital goods for one’s own enjoyment, to producing and trading them for profit. This chapter argues that NFTs manifest the full circle of the economy of signs: From consumption to “prosumption” and back to production of signs, where consumers are only implied and not necessarily present. The earlier “society of producers,” in Zigmund Bauman’s words, makes a comeback in the shape of a community where most members frantically produce content, rather than consume it. Such an “economy without a consumer” poses an interesting challenge to ever-accelerating post-capitalist economies.
Keywords: science and technology studies; virtual economies; fi=Viestintätieteet|en=Communication Studies|